K-Zn composite carbon-based catalyst, preparation method thereof and application of K-Zn composite carbon-based catalyst in synthesis of 1, 2-difluoroethylene

By preparing a K-Zn composite carbon-based catalyst, the problems of low efficiency and low yield of the target product of existing catalysts in the preparation of 1,2-difluoroethylene are solved, and the effect of efficient preparation of 1,2-difluoroethylene is achieved.

CN119346095APending Publication Date: 2025-01-24ZHEJIANG NORMAL UNIV +1

Patent Information

Application Number
CN202411481922.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing catalysts have low efficiency in preparing 1,2-difluoroethylene, low yield of target products, and high selectivity of by-products, resulting in no implementation value in the process.

Method used

K-Zn composite carbon-based catalyst is used. The catalyst synthesizes zinc-based anionic metal-organic framework materials (Zn-MOFs), performs ion exchange with potassium salt, and activates it in HCl-containing gas to obtain high-performance K-Zn Composite carbon-based catalyst.

Benefits of technology

A significant improvement of the efficiency of 1,2-dichlorophylhylene and HF reaction and HCL reaction was achieved, and the target product was high-revenue of 1,2-diofluorolythane, reduced the process process, and improved the response efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346095A_ABST
    Figure CN119346095A_ABST
Patent Text Reader

Abstract

The invention provides a K-Zn composite carbon-based catalyst, a preparation method thereof and application of the K-Zn composite carbon-based catalyst in synthesis of 1, 2-difluoroethylene, and belongs to the technical field of hydrofluoroolefin synthesis. The preparation method comprises the following steps: firstly synthesizing a zinc-based anionic metal organic framework material (Zn-MOFs), then performing ion exchange with sylvite, and performing activating treatment in HCl-containing gas to obtain the K-Zn composite carbon-based catalyst. According to the invention, Zn-MOFs is adopted as a catalyst precursor, dimethylamine cations in the structure of the Zn-MOFs are subjected to ion exchange with potassium ions, and activation treatment is carried out in HCl gas to obtain the high-performance surface chlorinated K-Zn composite carbon-based catalyst. According to the prepared K-Zn composite carbon-based catalyst, 1, 2-dichloroethylene and HF can be subjected to HF addition reaction and HCl removal reaction, the target product 1, 2-difluoroethylene can be prepared through one-step reaction, the technological process is greatly shortened, and the reaction efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrofluoroolefin synthesis, and in particular to a K-Zn composite carbon-based catalyst and a preparation method thereof and application thereof in the synthesis of 1,2-difluoroethylene. Background Art

[0002] The boiling point and critical temperature of trans-1,2-difluoroethylene (HFO-1132E) are -35.66℃ and 97.36℃ respectively, the critical pressure is 5089.3kPa, and the global warming potential (GWP) is 1, making it an ideal new generation refrigerant molecule. The preparation of HFO-1132 from cheap 1,2-dichloroethylene (HCO-1130) is expected to significantly reduce the manufacturing cost of HFO-1132. To this end, scientists have developed a variety of reaction systems. For example, patent CN112105594A reports that HCO-1130 can obtain HFO-1132 by continuously undergoing fluorine-chlorine exchange reaction and HF removal reaction in three reactors under the action of CrO2 catalyst after fluorination. However, due to the long reaction process, the final HFO-1132 yield is less than 2% (as shown in the following reaction formula 1). Patent CN115667191 reports that HFO-1132 is prepared by directly reacting HCO-1130 with metal fluorides such as KF, CsF or AgF. However, due to the low activity of metal fluorides, the yield of HFO-1132 in the reported processes is less than 2%, and the selectivity of by-products exceeds 90%. These processes are not yet worth implementing.

[0003]

[0004] Therefore, it is of great significance to develop a catalyst for the efficient reaction of HCO-1130 to prepare HFO-1132. Summary of the invention

[0005] The purpose of the present invention is to provide a K-Zn composite carbon-based catalyst and a preparation method thereof and application in the synthesis of 1,2-difluoroethylene, so as to solve the problems of low efficiency of existing catalysts and low yield of target products.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a K-Zn composite carbon-based catalyst, comprising the following steps:

[0008] The zinc salt, the organic ligand and the first amide solvent are mixed and crystallized to obtain Zn-MOFs;

[0009] Dispersing the Zn-MOFs and potassium salt in a second amide solvent, performing ion exchange, and obtaining K-Zn-MOFs;

[0010] The K-Zn-MOFs are activated in a gas containing HCl to obtain a K-Zn composite carbon-based catalyst.

[0011] Preferably, the zinc salt includes zinc acetate, zinc nitrate, zinc sulfate or zinc chloride; the organic ligand includes terephthalic acid, 4,4'-biphenyl dicarboxylic acid, benzotriazole-5-carboxylic acid, 2-pyridine carboxaldehyde, 2-amino-1,4-benzenedicarboxylic acid, bis(4-phenylimidazolyl)benzenesulfonone, 4,8-disulfonic-2,6-naphthalene dicarboxylic acid, 4,4',4"-nitro tribenzoic acid, 1,2,4-triazole, 2,4,6-tris(4-carboxyphenoxy)-1,3,5-triazine or adenine; and the molar ratio of the zinc salt to the organic ligand is 0.5 to 5:1.

[0012] Preferably, the first amide solvent and the second amide solvent are independently N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide;

[0013] The concentration of the zinc salt in the first amide solvent is 0.01-0.2 mol / L; the crystallization temperature is 100-150° C., and the crystallization time is 12-36 hours.

[0014] Preferably, the potassium salt includes potassium nitrate, potassium acetate, potassium sulfate or potassium chloride; the concentration of the potassium salt in the second amide solvent is 0.01 to 0.1 mol / L, and the concentration of the Zn-MOFs in the second amide solvent is 1 to 10 g / L;

[0015] The ion exchange time is 12 to 36 hours.

[0016] Preferably, the HCl-containing gas is a mixture of HCl and an auxiliary gas, and the auxiliary gas is N2, He or Ar; the volume content of HCl in the HCl-containing gas is 10 to 90%.

[0017] Preferably, the temperature of the activation treatment is 200-350° C., and the time is 2-6 hours; the heating rate to the temperature of the activation treatment is 0.5-5° C. / min.

[0018] The present invention provides a K-Zn composite carbon-based catalyst prepared by the preparation method described in the above technical scheme.

[0019] The present invention provides the use of the K-Zn composite carbon-based catalyst described in the above technical solution in catalyzing the synthesis of 1,2-dichloroethylene into 1,2-difluoroethylene.

[0020] Preferably, the application method comprises the following steps: gasifying 1,2-dichloroethylene, mixing it with HF gas, carrying out addition reaction under the action of K-Zn composite carbon-based catalyst, and washing the obtained gas with alkali to obtain 1,2-difluoroethylene.

[0021] Preferably, the volume ratio of 1,2-dichloroethylene to HF is 0.8-1.2:1; the conditions of the addition reaction include: reaction temperature of 250-350°C, reaction pressure of 1-5 bar, volume space velocity of 1,2-dichloroethylene of 500-5000h -1 .

[0022] The invention provides a method for preparing a K-Zn composite carbon-based catalyst. The invention first synthesizes a zinc-based anionic metal organic framework material (Zn-MOFs, the skeleton is anionic, the corresponding dimethylamine cation exists in the middle of the skeleton, and the material as a whole maintains electrical neutrality), then performs ion exchange with potassium salt, and performs activation treatment in HCl-containing gas to obtain a K-Zn composite carbon-based catalyst. The invention adopts Zn-MOFs as a catalyst precursor, the dimethylamine cation in the structure is ion exchanged with potassium ions, and then the surface is chlorinated in HCl gas. After chlorination, the material can be effectively activated by adsorption with Cl in the raw material dichloroethylene in the catalytic reaction, and Zn / K-MOFs is carbonized during the activation treatment process, that is, chlorination and carbonization reactions occur simultaneously, Zn and K are partially chlorinated, and the MOFs skeleton is carbonized, thereby obtaining a high-performance K-Zn composite carbon-based catalyst.

[0023] Compared with the K-Zn catalyst obtained by the conventional impregnation method, the K and Zn active centers on the catalyst surface obtained by the present invention undergo electron transfer (see Figure 2 The XPS results in Figure 2 show that the catalyst can efficiently remove HCl. The catalyst carbonized with MOF precursor produces a large number of acid center active sites (see Figure 3 The suitable acid center on the catalyst is conducive to the HCl removal reaction of the catalyst, thus Figure 1 The reaction process in the invention converts the HCO-1130 raw material into the target product HFO-1132E. Therefore, the K-Zn composite carbon-based catalyst prepared in the invention can make 1,2-dichloroethylene react with HF to undergo HF addition reaction and HCl removal reaction, and the target product 1,2-difluoroethylene can be obtained by one-step reaction, which greatly reduces the process flow, improves the reaction efficiency, and can solve the problems of low catalyst efficiency and low target product yield in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Reaction diagram for the conversion of HCO-1130 to produce HFO-1132E;

[0025] Figure 2 This is the XPS graph of the surface-chlorinated K-Zn / C catalyst prepared in Example 1;

[0026] Figure 3 This is the NH3-TPD diagram of the surface-chlorinated K-Zn / C catalyst prepared in Example 1. DETAILED DESCRIPTION

[0027] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0028] The present invention provides a method for preparing a K-Zn composite carbon-based catalyst, comprising the following steps:

[0029] The zinc salt, the organic ligand and the first amide solvent are mixed and crystallized to obtain Zn-MOFs;

[0030] Dispersing the Zn-MOFs and potassium salt in a second amide solvent, performing ion exchange, and obtaining K-Zn-MOFs;

[0031] The K-Zn-MOFs are activated in a gas containing HCl to obtain a K-Zn composite carbon-based catalyst.

[0032] In the present invention, the zinc salt preferably includes zinc acetate, zinc nitrate, zinc sulfate or zinc chloride, and more preferably zinc nitrate or zinc chloride; the organic ligand preferably includes terephthalic acid, 4,4'-biphenyl dicarboxylic acid, benzotriazole-5-carboxylic acid, 2-pyridine carboxaldehyde, 2-amino-1,4-phthalic acid, bis(4-phenylimidazolyl)benzenesulfonone, 4,8-disulfonic acid-2,6-naphthalene dicarboxylic acid, 4,4',4"-nitro tribenzoic acid, 1,2,4-triazole, 2,4,6-tris(4-carboxyphenoxy)-1,3,5-triazine or adenine, and more preferably 4,8-disulfonic acid-2,6-naphthalene dicarboxylic acid, 2-pyridine carboxaldehyde, bis(4-phenylimidazolyl)benzenesulfonone or adenine, and further preferably adenine.

[0033] In the present invention, the molar ratio of the zinc salt to the organic ligand is preferably 0.5 to 5:1, more preferably 0.6 to 3:1, and further preferably 1.2 to 2:1.

[0034] In the present invention, the first amide solvent and the second amide solvent are independently preferably N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA) or N,N-diethylformamide (DEF), and more preferably N,N-dimethylformamide (DMF).

[0035] In the present invention, the concentration of the zinc salt in the first amide solvent is preferably 0.01 to 0.2 mol / L, more preferably 0.05 to 0.15 mol / L; the crystallization temperature is preferably 100 to 150°C, preferably 110 to 140°C, more preferably 115 to 125°C; the time is preferably 12 to 36 h, more preferably 15 to 30 h, more preferably 20 to 25 h; the crystallization is preferably carried out in a polytetrafluoroethylene-lined high-pressure reactor.

[0036] In the present invention, a too large molar ratio of zinc salt to ligand will lead to excess zinc salt, generating more metal centers, thereby reducing the yield, specific surface area and porosity of the catalyst; at the same time, the excess zinc salt occupies the metal sites in MOFs, affecting the efficiency and selectivity of Zn-MOFs ion exchange. If the crystallization time is too long, the crystals will grow excessively to form larger crystals, which will reduce the specific surface area and porosity, affecting the adsorption and catalytic performance of MOFs; insufficient crystallization time will lead to incomplete crystal growth, forming smaller crystals or amorphous substances, which will reduce the crystallinity and stability of MOFs.

[0037] After the crystallization is completed, the present invention preferably filters, washes and dries the obtained product in sequence to obtain a Zn-based anionic metal organic framework material (Zn-MOFs).

[0038] In the present invention, the potassium salt preferably includes potassium nitrate, potassium acetate, potassium sulfate or potassium chloride, more preferably potassium nitrate or potassium chloride; the concentration of the potassium salt in the second amide solvent is preferably 0.01-0.1 mol / L, more preferably 0.02-0.08 mol / L, and further preferably 0.03-0.05 mol / L, and the concentration of the Zn-MOFs in the second amide solvent is preferably 1-10 g / L, more preferably 3-9 g / L, and further preferably 4-8 g / L. The present invention has no special limitation on the dispersion, and the materials can be mixed uniformly according to the process well known in the art.

[0039] In the present invention, the temperature of the ion exchange is preferably room temperature, and the time is preferably 12 to 36 hours, more preferably 16 to 30 hours, and further preferably 18 to 24 hours.

[0040] The present invention preferably places K-Zn-MOFs in a quartz tube and performs activation treatment in a gas containing HCl to obtain a K-Zn composite carbon-based catalyst.

[0041] During the ion exchange process, part of the dimethylamine ions are exchanged by potassium ions, and the remaining dimethylamine still exists in the Zn-MOFs. However, the remaining dimethylamine is burned away with the skeleton MOFs during the activation carbonization process, and no dimethylamine ions exist on the finally prepared K-Zn / C catalyst.

[0042] In the present invention, the HCl-containing gas is preferably a mixture of HCl and an auxiliary gas, the auxiliary gas is preferably N2, He or Ar, and more preferably He; the volume content of HCl in the HCl-containing gas is preferably 10 to 90%, more preferably 20 to 80%, and more preferably 30 to 60%.

[0043] In the present invention, if the HCl content in the HCl-containing gas is too high, the final catalyst will be converted into KCl and ZnCl2 with no catalytic performance during the activation process, and the melting point of ZnCl2 is only 283°C, which causes Zn to be lost during the activation process, thereby affecting the final catalytic performance; and if the HCl content is too low, the catalyst will have an insufficient degree of chlorination, causing K and Zn in the catalyst to exist in the form of K2O and ZnO with low catalytic performance, thereby reducing the final catalytic performance.

[0044] In the present invention, the temperature of the activation treatment is preferably 200-350°C, more preferably 220-300°C, and further preferably 240-280°C. The time is preferably 2-6h, and more preferably 3-5h. The heating rate to the temperature of the activation treatment is preferably 0.5-5°C / min, more preferably 2-4°C / min, and further preferably 2.5-3.5°C / min.

[0045] The present invention provides a K-Zn composite carbon-based catalyst prepared by the preparation method described in the above technical scheme.

[0046] The present invention provides the use of the K-Zn composite carbon-based catalyst described in the above technical solution in catalyzing the synthesis of 1,2-dichloroethylene into 1,2-difluoroethylene.

[0047] In the present invention, if Figure 1 As shown in the figure, 1,2-dichloroethylene (HCO-1130) is not directly produced by a fluorine-chlorine exchange reaction to obtain the product 1,2-difluoroethylene (HFO-1132), but is achieved by a continuous HF addition reaction and a HCl removal reaction on a catalyst. Generally, the HF addition reaction is easier to carry out, and the HF addition reaction can occur as long as the catalyst has a certain acid strength and acid sites; however, the HCl removal reaction is relatively difficult, and the selectivity of the HF addition reaction is not easy to control, such as Figure 1HCFO-1131Z (cis-1-chloro-2-fluoro-ethylene) can be subjected to HF addition reaction to obtain two products: HCFC-142a (1-chloro-1,2-difluoroethane) and HCFC-142 (2-chloro-1,1-difluoroethane). The product of the latter after dehydrochlorination is HFO-1132A, and HFO-1132E cannot be obtained (HFC-143 is a by-product of the addition reaction of 1132 with HF). The key points of the K-Zn composite carbon-based catalyst of the present invention for preparing 1,2-difluoroethylene by one-step reaction are as follows: 1) the K-Zn composite carbon-based catalyst is conducive to the efficient dehydrochlorination reaction of chloroalkanes (reactions 2 and 4); 2) K or Zn in the K-Zn composite carbon-based catalyst has a special valence electron state, which can improve the reaction selectivity and is conducive to the HF selective addition reaction of chloroolefins (reaction 3 occurs and reaction 5 is inhibited); 3) by accurately controlling the HF content in the reaction raw materials, the further HF addition reaction of HFO-1132 is inhibited, thereby reducing the selectivity of the by-product HFC-143 (i.e., reaction 7 is inhibited).

[0048] In the present invention, the application method preferably includes the following steps: gasifying 1,2-dichloroethylene (HCO-1130), mixing it with HF gas, performing an addition reaction under the action of a K-Zn composite carbon-based catalyst, and washing the obtained gas with alkali to obtain 1,2-difluoroethylene (HFO-1132E).

[0049] In the present invention, the volume ratio of 1,2-dichloroethylene to HF is preferably 0.8-1.2:1, more preferably 0.85-1.1:1, and further preferably 0.9-1.05:1; the conditions of the addition reaction preferably include: reaction temperature of 250-350°C, reaction pressure of 1-5 bar, volume space velocity of 1,2-dichloroethylene of 500-5000h -1 The addition reaction is carried out in a fixed bed reactor. The temperature of the addition reaction is more preferably 270-330°C, and more preferably 290-310°C. The reaction pressure is more preferably 1-4 bar, and more preferably 2-3 bar. The volume space velocity of 1,2-dichloroethylene is more preferably 500-4000 h -1 , more preferably 2000~3500h -1 .

[0050] The present invention has no particular limitation on the alkali washing, and the alkali washing can be carried out according to the process well known in the art.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] 7.5 mmol zinc nitrate and 12.5 mmol adenine were mixed and dissolved in 150 mL N,N-dimethylformamide (DMF), wherein the concentration of zinc salt in the solution was 0.05 mol / L, and the molar ratio of zinc salt to ligand adenine was 0.6:1, and the obtained mixture was transferred to a polytetrafluoroethylene liner of a high-pressure reactor, crystallized at 100° C. for 15 h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0054] 0.015 g of the above Zn-MOFs and 0.15 mmol of potassium chloride were dispersed in 15 mL of N,N-dimethylformamide (DMF), wherein the concentration of Zn-MOFs was 1 g / L and the concentration of potassium salt was 0.01 mol / L. The resulting dispersion was stirred at room temperature for 12 h for ion exchange to obtain K-Zn-MOFs.

[0055] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 200°C at a heating rate of 1°C / min, and activated in an atmosphere containing 20% ​​HCl gas (20% HCl by volume, the balance being He) for 2 hours to obtain a K-Zn / C catalyst.

[0056] Example 2

[0057] 6.3 mmol zinc chloride and 6.3 mmol 1,2,4-triazole were mixed and dissolved in 125 mL N,N-dimethylacetamide (DMA), wherein the concentration of zinc salt in the solution was 0.05 mol / L, and the molar ratio of zinc salt to ligand 1,2,4-triazole was 1:1, and the obtained mixture was transferred to a polytetrafluoroethylene liner of a high-pressure reactor, crystallized at 105° C. for 18 h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0058] 0.025 g of the above Zn-MOFs and 0.25 mmol of potassium nitrate were dispersed in 12.5 mL of N,N-dimethylacetamide (DMA), wherein the concentration of Zn-MOFs was 2 g / L and the concentration of potassium salt was 0.02 mol / L. The resulting dispersion was stirred at room temperature for 14 h for ion exchange to obtain K-Zn-MOFs.

[0059] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 220°C at a heating rate of 3°C / min, and activated in a 30% HCl gas atmosphere (30% HCl by volume, the remainder being He) for 4 hours to obtain a K-Zn / C catalyst.

[0060] Example 3

[0061] 7.5 mmol zinc acetate and 6.3 mmol adenine were mixed and dissolved in 100 mL N,N-diethylformamide (DEF), wherein the concentration of zinc salt in the solution was 0.075 mol / L, and the molar ratio of zinc salt to ligand adenine was 1.2:1. The obtained mixture was transferred to a polytetrafluoroethylene liner of an autoclave, crystallized at 110° C. for 20 h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0062] 0.03 g of the above Zn-MOFs and 0.3 mmol of potassium acetate were dispersed in 10 mL of N,N-diethylformamide (DEF), wherein the concentration of Zn-MOFs was 3 g / L and the concentration of potassium salt was 0.03 mol / L. The resulting dispersion was stirred at room temperature for 16 h for ion exchange to obtain K-Zn-MOFs.

[0063] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 240°C at a heating rate of 5°C / min, and activated for 5 hours in an atmosphere containing 40% HCl gas (40% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0064] Example 4

[0065] 5.6mmol zinc nitrate and 3.5mmol 1,2,4-triazole were mixed and dissolved in 75mL N,N-dimethylformamide (DMF), wherein the concentration of zinc salt in the solution was 0.075mol / L, and the molar ratio of zinc salt to ligand 1,2,4-triazole was 1.6:1, and the obtained mixture was transferred to a polytetrafluoroethylene liner of a high-pressure reactor for reaction, crystallized at 115°C for 22h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0066] 0.03 g of the above Zn-MOFs and 0.3 mmol of potassium chloride were dispersed in 7.5 mL of N,N-dimethylformamide (DMF), wherein the concentration of Zn-MOFs was 4 g / L and the concentration of potassium salt was 0.04 mol / L. The resulting dispersion was stirred at room temperature for 18 h for ion exchange to obtain K-Zn-MOFs.

[0067] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 260°C at a heating rate of 2°C / min, and activated for 2 hours in an atmosphere containing 50% HCl gas (50% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0068] Example 5

[0069] 5 mmol zinc chloride and 2.8 mmol adenine were mixed and dissolved in 50 mL N,N-dimethylformamide (DMF), wherein the concentration of zinc salt in the solution was 0.1 mol / L, and the molar ratio of zinc salt to ligand adenine was 1.8:1, and the obtained mixture was transferred to a polytetrafluoroethylene liner of an autoclave, crystallized at 120°C for 24 hours, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0070] 0.025 g of the above Zn-MOFs and 0.25 mmol of potassium chloride were dispersed in 5 mL of N,N-dimethylformamide (DMF), wherein the concentration of Zn-MOFs was 5 g / L and the concentration of potassium salt was 0.05 mol / L. The resulting dispersion was stirred at room temperature for 20 h for ion exchange to obtain K-Zn-MOFs.

[0071] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 280°C at a heating rate of 0.5°C / min, and activated for 3 hours in an atmosphere containing 60% HCl gas (60% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0072] Example 6

[0073] 15 mmol zinc acetate and 7.5 mmol adenine were mixed and dissolved in 100 mL N,N-dimethylformamide (DMF), wherein the concentration of zinc salt in the solution was 0.15 mol / L, and the molar ratio of zinc salt to ligand adenine was 2:1. The obtained mixture was transferred to a polytetrafluoroethylene liner of an autoclave, crystallized at 125°C for 26 hours, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0074] 0.06 g of the above Zn-MOFs and 0.6 mmol of potassium nitrate were dispersed in 10 mL of N,N-dimethylformamide (DMF), wherein the concentration of Zn-MOFs was 6 g / L and the concentration of potassium salt was 0.06 mol / L, and the obtained dispersion was stirred at room temperature for 22 h for ion exchange to obtain K-Zn-MOFs;

[0075] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 300°C at a heating rate of 4°C / min, and activated for 6 hours in an atmosphere containing 60% HCl gas (60% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0076] Example 7

[0077] 30mmol zinc chloride and 13.6mmol 1,2,4-triazole were mixed and dissolved in 150mL N,N-dimethylacetamide (DMA), wherein the concentration of zinc salt in the solution was 0.2mol / L, and the molar ratio of zinc salt to ligand 1,2,4-triazole was 2.2:1, and the obtained mixture was transferred to a polytetrafluoroethylene liner of a high-pressure reactor, crystallized at 130°C for 28h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0078] 0.105 g of the above Zn-MOFs and 1.05 mmol of potassium chloride were dispersed in 15 mL of N,N-dimethylacetamide (DMA), wherein the concentration of Zn-MOFs was 7 / L and the concentration of potassium salt was 0.07 mol / L. The resulting dispersion was stirred at room temperature for 24 h for ion exchange to obtain K-Zn-MOFs;

[0079] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 320°C at a heating rate of 3.5°C / min, and activated for 3 hours in an atmosphere containing 45% HCl gas (45% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0080] Example 8

[0081] 9.4 mmol zinc chloride and 3.3 mmol adenine were mixed and dissolved in 75 mL N,N-diethylformamide (DEF), wherein the concentration of zinc salt in the solution was 0.125 mol / L, and the molar ratio of zinc salt to ligand adenine was 2.8:1. The obtained mixture was transferred to a polytetrafluoroethylene liner of an autoclave, crystallized at 140°C for 30 h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0082] 0.12 g of the above Zn-MOFs and 1.2 mmol of potassium chloride were dispersed in 15 mL of N,N-diethylformamide (DEF), wherein the concentration of Zn-MOFs was 8 g / L and the concentration of potassium salt was 0.08 mol / L. The obtained dispersion was stirred at room temperature for 32 h for ion exchange to obtain K-Zn-MOFs.

[0083] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 330°C at a heating rate of 2.5°C / min, and activated for 5 hours in an atmosphere containing 35% HCl gas (35% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0084] Example 9

[0085] 7.5 mmol zinc acetate and 2.5 mmol adenine were mixed and dissolved in 50 mL N,N-diethylformamide (DEF), wherein the concentration of zinc salt in the solution was 0.15 mol / L, and the molar ratio of zinc salt to ligand adenine was 3:1. The obtained mixture was transferred to a polytetrafluoroethylene liner of an autoclave, crystallized at 150°C for 25 h, filtered, washed, and dried to obtain a Zn-based anionic metal organic framework material (Zn-MOFs);

[0086] 0.15 g of the above Zn-MOFs and 1.5 mmol of potassium chloride were dispersed in 15 mL of N,N-diethylformamide (DEF), wherein the concentration of Zn-MOFs was 10 g / L and the concentration of potassium salt was 0.1 mol / L. The obtained dispersion was stirred at room temperature for 36 h for ion exchange to obtain K-Zn-MOFs.

[0087] The above-mentioned K-Zn-MOFs were placed in a quartz tube, heated to 350°C at a heating rate of 3.5°C / min, and activated for 6 hours in an atmosphere containing 55% HCl gas (55% HCl by volume, the remainder being He) to obtain a K-Zn / C catalyst.

[0088] The K-Zn / C catalysts prepared in Examples 1 to 9 are denoted as AI respectively.

[0089] Example 10

[0090] 60 mg of the prepared K-Zn / CA catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 250°C for reaction, wherein the gas after the reaction was passed into 5L of 0.1mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0091] Embodiment 11

[0092] 50 mg of the prepared K-Zn / CB catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=85:100, and the space velocity of HCO-1130=2000h -1The reaction pressure was 3 bar, and the temperature was raised to 260°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0093] Example 12

[0094] 40 mg of the prepared K-Zn / CC catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=90:100, and the space velocity of HCO-1130=4000h -1 The reaction pressure was 4.5 bar, and the temperature was raised to 270°C for reaction. The gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein to obtain 1,2-difluoroethylene (HFO-1132E).

[0095] Example 13

[0096] 40 mg of the prepared K-Zn / CD catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=95:100, and the space velocity of HCO-1130=3500h -1 The reaction pressure was 3 bar, and the temperature was raised to 290°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0097] Embodiment 14

[0098] 30 mg of the prepared K-Zn / CE catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=100:100, and the space velocity of HCO-1130=5000h -1 The reaction pressure was 5 bar, and the temperature was raised to 310°C for reaction. The gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases to obtain 1,2-difluoroethylene (HFO-1132E).

[0099] Embodiment 15

[0100] 30 mg of the prepared K-Zn / CF catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=105:100, and the space velocity of HCO-1130=500h -1 The reaction pressure was 1 bar, and the temperature was raised to 320°C for reaction. The gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein to obtain 1,2-difluoroethylene (HFO-1132E).

[0101] Example 16

[0102] 20 mg of the prepared K-Zn / CG catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=110:100, and the space velocity of HCO-1130=2500h -1 The reaction pressure was 3 bar, and the temperature was raised to 330°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0103] Embodiment 17

[0104] 10 mg of the prepared K-Zn / CH catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=120:100, and the space velocity of HCO-1130=4000h -1 The reaction pressure was 2.5 bar, and the temperature was raised to 340°C for reaction. The gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein to obtain 1,2-difluoroethylene (HFO-1132E).

[0105] Embodiment 18

[0106] 10 mg of the prepared K-Zn / CI catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=100:100, and the space velocity of HCO-1130=4500h -1The reaction pressure was 4 bar, and the temperature was raised to 350°C for reaction. The gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein to obtain 1,2-difluoroethylene (HFO-1132E).

[0107] Comparative Example 1

[0108] 7.5 mmol zinc nitrate was dissolved in 150 mL deionized water, wherein the concentration of zinc salt in the solution was 0.05 mol / L; 0.1 g activated carbon was used as a carrier, 600 μL zinc nitrate solution was added and the mixture was impregnated with an equal volume method for 12 h, placed in a crucible and dried at 10°C for 12 h, and calcined at 400°C for 3 h under a nitrogen atmosphere to obtain a zinc-containing carbon catalyst, which was recorded as C-1.

[0109] 10 mg of the prepared C-1 catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 350°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0110] Comparative Example 2

[0111] 1.5 mmol potassium chloride was dissolved in 150 mL deionized water, wherein the concentration of potassium salt in the solution was 0.01 mol / L; 0.1 g activated carbon was used as a carrier, 600 μL potassium chloride solution was added and the mixture was impregnated with an equal volume method for 12 h, placed in a crucible and dried at 10°C for 12 h, and calcined at 400°C for 3 h under a nitrogen atmosphere to obtain a potassium-containing carbon catalyst, which was recorded as C-2.

[0112] 10 mg of the prepared C-2 catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 350°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0113] Comparative Example 3

[0114] 7.5mmol zinc nitrate and 1.5mmol potassium chloride were dissolved in 150mL deionized water, wherein the concentration of the salt in the solution was 0.05mol / L, and the concentration of the potassium salt in the solution was 0.01mol / L; 0.1g activated carbon was used as a carrier, 600μL of the mixed solution was added and impregnated with equal volume for 12h, placed in a crucible and dried at 10℃ for 12h, and calcined at 400℃ for 3h under a nitrogen atmosphere to obtain a potassium-containing carbon catalyst, which was recorded as C-3.

[0115] 10 mg of the prepared C-3 catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 350°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0116] Comparative Example 4

[0117] The difference from Example 10 is that the reaction temperature is 200°C.

[0118] 60 mg of the prepared K-Zn / CA catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 200°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0119] Comparative Example 5

[0120] The difference from Example 10 is that the catalytic reaction temperature is 400°C.

[0121] 60 mg of the prepared K-Zn / CA catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1The reaction pressure was 2 bar, and the temperature was raised to 400°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0122] Comparative Example 6

[0123] The difference from Example 10 is that in the catalytic reaction, v(HCO-1130):v(HF)=50:100.

[0124] 60 mg of the prepared K-Zn / CA catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=50:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 400°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0125] Comparative Example 7

[0126] The difference from Example 10 is that in the catalytic reaction, v(HCO-1130):v(HF)=150:100.

[0127] 60 mg of the prepared K-Zn / CA catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 400°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0128] Comparative Example 8

[0129] 7.5mmol zinc nitrate and 1.5mmol potassium nitrate were dissolved in 150mL deionized water, wherein the concentration of the salt in the solution was 0.05mol / L, and the concentration of the potassium salt in the solution was 0.01mol / L; 0.1g activated carbon was used as a carrier, 600μL of the mixed solution was added, and the mixture was impregnated with an equal volume method for 12h, placed in a crucible and dried at 10℃ for 12h, and calcined at 400℃ for 3h in a nitrogen atmosphere to obtain a zinc-potassium carbon catalyst K2O-ZnO / C, which was recorded as C-4.

[0130] 10 mg of the prepared C-4 catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 350°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132E).

[0131] Comparative Example 9

[0132] 7.5mmol zinc chloride and 1.5mmol potassium chloride were dissolved in 150mL deionized water, wherein the concentration of the salt in the solution was 0.05mol / L, and the concentration of the potassium salt in the solution was 0.01mol / L; 0.1g activated carbon was used as a carrier, 600μL of the mixed solution was added and impregnated with an equal volume method for 12h, placed in a crucible and dried at 10℃ for 12h, and calcined at 200℃ under a nitrogen atmosphere for 3h to obtain a zinc-potassium carbon catalyst KCl-ZnCl2 / C, which was recorded as C-5.

[0133] 10 mg of the prepared C-5 catalyst was placed in a fixed bed reactor, and gasified 1,2-dichloroethylene (HCO-1130) and HF gas were introduced, wherein v(HCO-1130):v(HF)=80:100, and the space velocity of HCO-1130=1500h -1 The reaction pressure was 2 bar, and the temperature was raised to 350°C for reaction, wherein the gas after the reaction was passed into 5 L of 0.1 mol / L NaOH aqueous solution for alkaline washing to remove HCl and HF acid gases therein, thereby obtaining 1,2-difluoroethylene (HFO-1132).

[0134] Performance Verification:

[0135] (1) The surface element state of K-Zn / C catalysts prepared in different cases was measured for the surface valence electron state and surface acidity:

[0136] Surface valence electron state test method: The test was conducted using the ESCALAB250X X-ray photoelectron spectrometer from Thermo Scientific, USA, with the X-ray source being Al's Kα (1486.6 eV). Test conditions: Vacuum conditions: 5.0*10 -7 Pa. X-ray photoelectron spectroscopy can be used to evaluate the valence state of the catalyst metal surface and other related information. 1s=283.8eV was used as the internal standard for charge compensation of other elements. When performing element scanning, the scanning step was 0.05eV and the pass energy was 20.0eV.

[0137] The surface acidity test method is performed on a Micromeritics AutoChem II 2920 instrument. 0.05g of the catalyst was heated to 400°C in He (30mL / min) at a heating rate of 10°C / min and maintained for 1h to ensure that the catalyst surface is clean. After the system temperature dropped to 50°C, 30mL / min of a 10% NH3 / He gas mixture was introduced into the catalyst bed at 50° for adsorption for 1h, and then switched to 30mL / min of He purge at 70°C for 1h to remove the gas physically adsorbed on the catalyst surface. The desorbed tail gas was detected online using a TCD detector. When the detection baseline was stable, the programmed temperature system was turned on and heated to 500°C at a heating rate of 10°C / min.

[0138] Figure 2 The K, Zn, and Cl element data results of the XPS test of the K-Zn / C catalyst prepared in Example 1 are as follows: Figure 2 As shown in 3 / 2 The binding energy is 293.3 eV, which deviates 0.4 eV from the standard binding energy (292.9 eV). 3 / 2 The binding energy is 1022.6eV, which deviates from the standard binding energy (1023.10eV) by 0.5eV, indicating that there is a certain electron transfer between Zn and K on the catalyst. On the other hand, there are two forms of Cl on the catalyst, namely organic chlorine and metal chloride. The valence electron states of K and Zn are different from both 0 and 1, which indicates the particularity of the valence electron states of the surface elements K, Zn and Cl of the catalyst obtained by this method.

[0139] Figure 3 The NH3-TPD data results of the K-Zn / C catalyst prepared in Example 1 are as follows: Figure 3 As shown in , the catalyst has two obvious desorption peaks at 150°C and 400°C, indicating that the catalyst has two acid sites with weak intensity and high intensity. These two acid sites are conducive to the catalyst to carry out efficient HCl removal reaction.

[0140] (3) Determine the specific surface area of ​​the K-Zn / C catalyst in Examples 1 to 9. The specific surface area of ​​the catalyst is tested using a physical adsorption instrument model ASAP2020 from Micromeritics, USA. The sample is first vacuum degassed at 150°C for 10 h, and then the sample is placed at -196°C for a N2 adsorption-desorption experiment to obtain a N2 adsorption-desorption curve. The BET (Brunauer-Emmett-Teller) calculation method is used to obtain the specific surface area data (m 2 / g), the test results are shown in Table 1.

[0141] The conversion rates of 1,2-difluoroethylene (HFO-1132) in Examples 10 to 18 and Comparative Examples 1 to 7 were measured. The results are shown in Table 2:

[0142] Calculation method of HFO-1132 product yield: A gas chromatograph from Thermo Scientific, USA, is used. The chromatograph is equipped with two detectors, a mass spectrometer (MS) detector and a hydrogen flame ionization detector (FID), which can perform qualitative and quantitative tests simultaneously. The products of each embodiment and comparative example were collected for analysis. The injection port temperature was 240° C., the column oven was maintained at 50° C. for 5 min, and then the temperature was increased to 150° C. at a heating rate of 5° C. / min and maintained for 5 min. The chromatographic column used a Gaspro capillary column, the chromatographic column was 30 m long, 0.25 mm in diameter, and 0.25 um in thickness. The chromatographic column carrier gas was helium, and the column flow rate was 0.5 mL / min. Qualitative analysis showed that there were raw material HCO-1130, target product HFO-1132, and by-products HCFC-141, HCFO-1131Z, HCFC-142a, HCFC-142, HFO-1132A, HFC-143 and the like in the mixed gas at the outlet of the reactor. The products were quantitatively analyzed by the area normalization method, and the conversion rate of the raw material HCO-1130 and the selectivity of the product HFO-1132 were calculated.

[0143] Table 1 Specific surface area test results of K-Zn / C catalysts of Examples 1 to 9

[0144] serial number <![CDATA[Specific surface area (m 2 / g)]]> Example 1 284 Example 2 194 Example 3 208 Example 4 254 Example 5 239 Example 6 187 Example 7 216 Example 8 243 Example 9 225

[0145] Table 2 Test results of HCO-1130 conversion and product HFO-1132E selectivity in Examples 10 to 18 and Comparative Examples 1 to 9

[0146]

[0147]

[0148] From the test results in Tables 1 and 2, it can be seen that the type of zinc salt, the type of organic ligand, the molar ratio of the two, the crystallization temperature, the crystallization time, and the type and concentration of potassium salt in the preparation process of K-Zn / C catalyst have an impact on the specific surface area of ​​K-Zn / C catalyst, and thus affect the product yield of 1,1-difluoroethylene prepared by HF addition reaction and HCl removal reaction of 1,2-dichloroethylene. In addition, the molar ratio of HCO-1130 to HF, the amount of catalyst, the reaction temperature, etc. also have a certain impact on the yield of 1,1-difluoroethylene.

[0149] As can be seen from the above embodiments, the present invention provides a method for preparing a K-Zn composite carbon-based catalyst, first synthesizing a zinc-based anionic metal organic framework material (Zn-MOFs), then performing ion exchange with potassium salt, and performing activation treatment in HCl-containing gas to obtain a K-Zn composite carbon-based catalyst. The present invention uses Zn-MOFs as a catalyst precursor, and the dimethylamine cations in its structure can be ion exchanged with potassium ions. The activation treatment in HCl gas can obtain a surface-chlorinated K-Zn / C catalyst. The prepared K-Zn composite carbon-based catalyst can cause 1,2-dichloroethylene to undergo HF addition reaction and de-HCl reaction to obtain the target product 1,1-difluoroethylene.

[0150] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a K-Zn composite carbon-based catalyst, characterized in that: The following steps are involved: The zinc salt, the organic ligand and the first amide solvent are mixed and crystallized to obtain Zn-MOFs; Dispersing the Zn-MOFs and potassium salt in a second amide solvent, performing ion exchange, and obtaining K-Zn-MOFs; The K-Zn-MOFs are activated in a gas containing HCl to obtain a K-Zn composite carbon-based catalyst.

2. The preparation method according to claim 1, characterized in that: The zinc salt includes zinc acetate, zinc nitrate, zinc sulfate or zinc chloride; the organic ligand includes terephthalic acid, 4,4'-biphenyl dicarboxylic acid, benzotriazole-5-carboxylic acid, 2-pyridine carboxaldehyde, 2-amino-1,4-benzenedicarboxylic acid, bis(4-phenylimidazolyl)benzenesulfonone, 4,8-disulfonic acid-2,6-naphthalenedicarboxylic acid, 4,4',4"-nitrotribenzoic acid, 1,2,4-triazole, 2,4,6-tris(4-carboxyphenoxy)-1,3,5-triazine or adenine; the molar ratio of the zinc salt to the organic ligand is 0.5 to 5:

1.

3. The preparation method according to claim 1 or 2, characterized in that: The first amide solvent and the second amide solvent are independently N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide; The concentration of the zinc salt in the first amide solvent is 0.01-0.2 mol / L; the crystallization temperature is 100-150° C., and the crystallization time is 12-36 hours.

4. The preparation method according to claim 1, characterized in that: The potassium salt includes potassium nitrate, potassium acetate, potassium sulfate or potassium chloride; the concentration of the potassium salt in the second amide solvent is 0.01-0.1 mol / L, and the concentration of the Zn-MOFs in the second amide solvent is 1-10 g / L; The ion exchange time is 12 to 36 hours.

5. The preparation method according to claim 1, characterized in that: The HCl-containing gas is a mixed gas of HCl and an auxiliary gas, and the auxiliary gas is N2, He or Ar; the volume content of HCl in the HCl-containing gas is 10-90%.

6. The preparation method according to claim 1 or 5, characterized in that: The activation treatment temperature is 200-350° C., and the time is 2-6 hours; the heating rate to the activation treatment temperature is 0.5-5° C. / min.

7. The K-Zn composite carbon-based catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the K-Zn composite carbon-based catalyst according to claim 7 in catalyzing the synthesis of 1,2-difluoroethylene from 1,2-dichloroethylene.

9. The use according to claim 8, characterized in that The application method comprises the following steps: gasifying 1,2-dichloroethylene, mixing it with HF gas, carrying out addition reaction under the action of K-Zn composite carbon-based catalyst, and washing the obtained gas with alkali to obtain 1,2-difluoroethylene.

10. The use according to claim 9, characterized in that: The volume ratio of 1,2-dichloroethylene to HF is 0.8-1.2:1; the conditions of the addition reaction include: the reaction temperature is 250-350°C, the reaction pressure is 1-5 bar, the volume space velocity of 1,2-dichloroethylene is 500-5000h -1 .

Citation Information

Patent Citations

  • Method for preparing 1,2-difluoroethylene and / or 1,1,2-trifluoroethane

    CN112105594A

Cited By

  • Potassium-containing bimetallic complex flame inhibitor as well as preparation method and application thereof

    CN121517723A